Komunikasi Kepemimpinan dalam Penyelesaian Konflik di Sekolah - Oktavia, Della Dhienytha; Hidayat, Wahyu (NIẒĀMUL`ILMI : Jurnal Manajemen Pendidikan Islam, 2024)
Effective leadership communication is very important in achieving organizational goals, including in the school context. The inability of school principals to resolve conflicts between teachers and students can cause serious problems that impact learning activities. At Kiyafatul Achyar High School, Bandung City, there was a conflict between teachers and students due to communication errors and non-technical disputes. The purpose of this research is to find out patterns, obstacles and solutions to leadership communication in conflict resolution at Kifayatul Achyar High School. This research uses a qualitative approach with descriptive methods. Research on leadership communication in conflict resolution at Kifayatul Achyar High School in Bandung City shows that interpersonal, group, and organizational communication patterns are used in conflict resolution. Obstacles faced include differences of opinion, lack of facilities, and teachers who teach outside their area of expertise. The proposed solutions involve deliberation, submission of proposals, and evaluation. This research is expected to encourage schools to optimize leadership communication skills, provide communication media, and increase activities that involve conflict resolution.